2012
DOI: 10.1021/ie3011879
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigations on the Electrostatics Generation and Transport in the Downer Reactor of a Triple-Bed Combined Circulating Fluidized Bed

Abstract: Electrostatics is an inevitable phenomenon in fluidization processes and granular flow systems where collisions between particulates and walls with different materials occur. In this study, the electrostatic performance in the downer reactor of a triple-bed combined circulating fluidized bed was investigated through both experiments and numerical simulations. In numerical simulation the Discrete Element Method (DEM) was adopted to simulate the electrostatic charge generation and transfer occurring in the downe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…With the same area, half-circle granular and rectangle granular tend to acquire the same electrostatic charge. This result agreed with the experimental findings by Cheng et al [9], who the electrostatics generation in the downer reactor and observed that the averages induced currents increased with particle diameter. In addition, this trend was also supported by experimental work on tribocharging of aerosols of fine phosphate rock concentrations done by Marra et al [22], who found that the generated charge of particles increased accordingly with the mean particle size, implying a greater extent of electrostatics.…”
Section: Influence Of Length-ratiosupporting
confidence: 93%
See 1 more Smart Citation
“…With the same area, half-circle granular and rectangle granular tend to acquire the same electrostatic charge. This result agreed with the experimental findings by Cheng et al [9], who the electrostatics generation in the downer reactor and observed that the averages induced currents increased with particle diameter. In addition, this trend was also supported by experimental work on tribocharging of aerosols of fine phosphate rock concentrations done by Marra et al [22], who found that the generated charge of particles increased accordingly with the mean particle size, implying a greater extent of electrostatics.…”
Section: Influence Of Length-ratiosupporting
confidence: 93%
“…On the other hand, the proper usage of electrostatics can be beneficial in many industrial processes, such as printing, and dust removal. Therefore, it is of great significance to study the electrostatic phenomenon in fluidization and granular flow system to mitigate its negative effects and utilize its positive effects [9]. Granular material is commonly used in solid-handling or pneumatic conveying systems in the energy, chemical, pharmaceutical, and material processing industries.…”
Section: Introductionmentioning
confidence: 99%
“…For both cases ( Fig.5(a),(b)), it is seen that the electrostatics (charge to length-ratio) increases with sliding area, which is independent of granule sliding-face shape. This result agrees well with the experimental findings by Cheng et al [25], who investigated electrostatics generation in a downer reactor and observed that the averaged induced currents increase with granule diameter. In addition, this conclusion also agrees well with the experiment work done by Marra et al [26], where they studied tribocharging of aerosols of fine phosphate rock concentrations and concluded that electrostatics charge generated increases with granule size.…”
Section: Sliding Area Effectsupporting
confidence: 93%
“…There are also reports regarding the CFD and/or discrete element method modeling incorporating the electrostatics/triboelectrification model for other fluidized bed reactors (FBRs) instead of FCC risers . Recently, Cheng et al . investigated the electrostatic performance in the downer reactor of a triple‐bed combined circulating FBR via experiments and numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…There are also reports regarding the CFD and/or discrete element method modeling incorporating the electrostatics/triboelectrification model for other fluidized bed reactors (FBRs) instead of FCC risers. [41][42][43][44][45][46][47][48] Recently, Cheng et al [41] investigated the electrostatic performance in the downer reactor of a triple-bed combined circulating FBR via experiments and numerical simulations. Rokkam et al [42] developed a first-principles electrostatic model and incorporated it into a multifluid CFD model to understand the effect of electrostatics in a polymerization FBR in their works.…”
Section: Introductionmentioning
confidence: 99%